Strategic analysis for advancing Morocco's nuclear infrastructure using PESTELE framework - Hafsa Housni; Naila Amrous; Najima Daoudi; Mohamed Jaouad Malzi (Nuclear Analysis)
Morocco's exploration of nuclear energy aligns with both climate goals and national energy ambitions, offering a promising low-carbon alternative to conventional fossil fuels. Despite the nation's significant strides in renewable energy, nuclear power remains understudied, revealing a critical literature gap. This research underscores the global imperative to transition to net-zero emissions and the pivotal role nuclear energy plays in addressing climate change. Within the context of Morocco's 2030 plan, which prioritizes renewable energy, nuclear energy stands as an underexplored aspect, lacking comprehensive research. To bridge this gap, the study employs a PESTLE analysis to examine the political, economic, societal, technological, legal, and environmental factors influencing Morocco's nuclear energy landscape. The integration of insights from various sources, including press releases, reports, and scientific publications, ensures a holistic and well-informed perspective on Morocco's nuclear industry. The paper concludes by providing an overview of nuclear energy use on different scales, accompanied by a detailed discussion of the PESTLE analysis outcomes. This approach seeks to contribute valuable insights for informed decision-making and strategic planning in the realm of nuclear energy development.